2015
DOI: 10.1123/pes.2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 12-Week Low vs. High Intensity Aerobic Exercise Training on Appetite-Regulating Hormones in Obese Adolescents: A Randomized Exercise Intervention Study

Abstract: Little is known about how the intensity of aerobic training influences appetite-regulating hormones in obese adolescents. Our goal was to assess the effect of low and high intensity aerobic trainings on food intake and appetite-regulating hormones in obese adolescents. Forty three obese adolescents (age: 13-18y, BMI: 34.48 ± 3.94 kg/m2) were randomized into high intensity training (HIT; n = 20) or low intensity training (LIT; n = 23) groups for 12 weeks. All participants also received the same nutritional, psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 36 publications
2
47
0
6
Order By: Relevance
“…Importantly, Masquio et al classified their population in tertiles according to changes in saturated fatty acid (SFA) by the end of intervention (low reduction in SFA, ‘Low‐SFA’; moderate reduction in SFA, ‘Moderate‐SFA’; and high reduction in SFA, ‘High‐SFA’) . While six studies were conducted in a clinical setting , one was laboratory‐based , and two were community‐based .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, Masquio et al classified their population in tertiles according to changes in saturated fatty acid (SFA) by the end of intervention (low reduction in SFA, ‘Low‐SFA’; moderate reduction in SFA, ‘Moderate‐SFA’; and high reduction in SFA, ‘High‐SFA’) . While six studies were conducted in a clinical setting , one was laboratory‐based , and two were community‐based .…”
Section: Resultsmentioning
confidence: 99%
“…All studies used self‐reported dietary records to assess energy intake, using 3‐d ; 4‐d , 24‐h or 48‐h recalls . Body composition was assessed whether by using skin‐folds air‐displacement plethysmography , biphotonic absorptiometry or bio‐electrical impedance analyses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that high intensity interval training may be a suitable exercise approach to improve vascular function in both lean and obese boys (3). Further, Prado and colleagues explored the effects of low versus high intensity exercise on food intake and appetite-regulating hormones in obese adolescents (16). Their results showed that food intake was reduced, and PYY was increased significantly in the high intensity exercise group but not in the low intensity group, whereas leptin and ghrelin were significantly reduced in both the light and high intensity exercise groups (16).…”
Section: Pennington Biomedical Research Centermentioning
confidence: 99%
“…Further, Prado and colleagues explored the effects of low versus high intensity exercise on food intake and appetite-regulating hormones in obese adolescents (16). Their results showed that food intake was reduced, and PYY was increased significantly in the high intensity exercise group but not in the low intensity group, whereas leptin and ghrelin were significantly reduced in both the light and high intensity exercise groups (16). The effects of short-term exercise with and without milk intake on cardiometabolic and inflammatory adaptations in obese adolescents was reported in Liu and colleagues (13).…”
Section: Pennington Biomedical Research Centermentioning
confidence: 99%